Community Empowerment in Flood Management through Biopori Infiltration Pits as a Means of Reducing Environmental Accounting Costs - Ersi Sisdianto; Wahyu Setyawan; Sri Suci Suryawati (Suluh Abdi: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
Flooding is a recurring issue in Beringin Jaya Village, Kemiling District, Bandar Lampung, causing economic losses and environmental damage. Conventional flood management often relies on costly infrastructure projects, which burden local governments with high environmental accounting costs. This community empowerment initiative introduces biopori infiltration pits as a sustainable, low-cost solution to improve water absorption, mitigate flooding, and reduce long-term environmental accounting expenses. Through participatory action research (PAR), the program trained residents in constructing and maintaining biopori pits, emphasizing community ownership and environmental stewardship. Pre and post intervention data showed a 30% increase in groundwater absorption capacity and a reduction in flood frequency in targeted areas. Additionally, the project lowered municipal costs for flood-related disaster response and infrastructure repairs, demonstrating how eco-friendly interventions can align with fiscal sustainability. This initiative highlights the role of community-based environmental accounting in disaster risk reduction, offering a scalable model for flood-prone regions. By integrating biopori technology with local governance, the program not only enhances ecological resilience but also alleviates financial burdens on public budgets.